2014
DOI: 10.1111/1755-6724.12216
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology, Geochemistry and Tectonic Setting of the Bairiqiete Granodiorite Intrusion (Rock Mass) from the Buqingshan Tectonic Mélange Belt in the Southern Margin of East Kunlun

Abstract: : This study focuses on the zircon U–Pb geochronology and geochemistry of the Bairiqiete granodiorite intrusion (rock mass) from the Buqingshan tectonic mélange belt in the southern margin of East Kunlun. The results show that the zircons are characterized by internal oscillatory zoning and high Th/U (0.14–0.80), indicative of an igneous origin. LA–ICP–MS U–Pb dating of zircons from the Bairiqiete granodiorite yielded an age of 439.0 ± 1.9 Ma (MSWD = 0.34), implying that the Bairiqiete granodiorite formed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…This inference indicates an active instead of a passive continental margin setting for the SW‐NCC. Deep‐water sedimentary rocks of the Permian to the Early Triassic in the west Qinling (Li et al, 2014, 2015; Zhang et al, 2019b) have been suggested to represent the forearc basin fill developed on the flanks of this continental arc (Liu et al, 2015; Qian, Liu, Li, Gao, & Chen, 2015; Qian, Liu, Wang, Li, & Chen, 2015; Yan et al, 2014). On the other hand, Zhang et al (2017) obtained weighted mean ages of 276.8 ± 7.9 Ma and 276.2 ± 9.7 Ma from diabase identified in the northeastern margin of the Qilian orogen.…”
Section: Discussionmentioning
confidence: 99%
“…This inference indicates an active instead of a passive continental margin setting for the SW‐NCC. Deep‐water sedimentary rocks of the Permian to the Early Triassic in the west Qinling (Li et al, 2014, 2015; Zhang et al, 2019b) have been suggested to represent the forearc basin fill developed on the flanks of this continental arc (Liu et al, 2015; Qian, Liu, Li, Gao, & Chen, 2015; Qian, Liu, Wang, Li, & Chen, 2015; Yan et al, 2014). On the other hand, Zhang et al (2017) obtained weighted mean ages of 276.8 ± 7.9 Ma and 276.2 ± 9.7 Ma from diabase identified in the northeastern margin of the Qilian orogen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches of the Early Palaeozoic magmatic rocks have shown that there are old island‐arc magmatic characteristics in the Buqingshan–A'nyemaqen Tectonic Mélange Belt (Bian et al ., , b; Liu, ; Liu et al ., , b). The ages of these magmatic rocks are divided into two phases: the early phase is the Cambrian–Furongian (such as De Dur'ngoi diorite; Li et al ., ), and the later phase is Early Silurian (such as Yikehalaer granodiorite, Bairiqiete granodiorite, and acidic volcanic lava; Bian et al ., ; Liu, ; Li et al ., , respectively). The formation ages of this Early Palaeozoic magmatic are similar to the subduction time of the Proto‐Tethyan Ocean.…”
Section: Introductionmentioning
confidence: 84%
“…This age is significantly later than that of the Buqingshan tectonic mélange Delisitan oceanic ridge ophiolite (gabbros aged 516.4 ± 6.3 to 467.2 ± 0.9 Ma; Bian et al ., ; Liu et al ., ), Majixueshan oceanic ridge ophiolite in the A'nyemaqen Tectonic Mélange Belt (535 ± 10 Ma) (Li et al ., ), Qingshuiquan ophiolite in the central eastern Kunlun Tectonic Mélange Belt (522.3 ± 4.1 to 507.7 ± 8.3 Ma) (Yang et al ., ; Lu et al ., ; Li et al ., ; Chen et al ., ; Ren et al ., ), and ancient ocean basin remnants of the Kekesha–Kekekete mafic–ultramafic mélange (509.4 ± 6.8 to 501 ± 7 Ma) (Feng et al ., ; Li et al ., ). This age is earlier than that of the Yikehalaer island‐arc granodiorite rock mass (437.5 ± 6.6 Ma to 402 ± 24 Ma; Bian et al ., ; Liu, ; Li et al ., ), the Bairiqiete island‐arc granodiorite (441.1 ± 6.3 Ma to 439.0 ± 1.9 Ma; Liu et al ., ; Li et al ., ), and acidic volcanic lava (437.7 ± 2.8 Ma; Liu et al ., ) in the Buqingshan–A'nyemaqen Early Palaeozoic Tectonic Mélange Belt, and similar to the Dur'ngoi island‐arc diorite age (493 ± 6 Ma; Li et al ., ). Finally, the post‐collision granitoids of the East Kunlun Orogen (411 ± 17 Ma to 394 ± 13 Ma; Liu et al , ; Zhao et al , ; Chen et al , ; Long et al , ), Helegangnaren A‐type granites of the north side of the East Kunlun Fault (425 ± 7 Ma, Li et al ., ), and the extension‐type molasse of the Maoniushan Formation in the north of East Kunlun Orogen and the northern margin of the Qaidam Basin (423.2 ± 1.8 Ma to 399.6 ± 2.8 Ma; Xu et al ., ; Li et al ., ; Lu et al ., ; Zhang et al , ) are significantly later than the Manite granodiorite.…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al (2015) showed that Late Triassic plagiogranite (~227 Ma) from the Shuangqing Fe–Pb–Zn–Cu deposit in the eastern EKOB was derived from the partial melting of thickening crustal materials in a post‐collisional tectonic setting caused by stress changes from compression to extension. Li et al (2013) proved that the Cozzo Tor diorite (225.8 ± 1.5 Ma) was derived from crustal melting after the collision between the East Kunlun and Bayan Har blocks in the post‐collision environment.…”
Section: Discussionmentioning
confidence: 99%